B Cell Dysregulation in Common Variable Immunodeficiency Interstitial Lung Disease - Matson, Erik M.; Abyazi, Miranda L.; Bell, Kayla A.; Hayes, Kevin M.; Maglione, Paul J. (Frontiers in Immunology, 2021)
Common variable immunodeficiency (CVID) is the most frequently diagnosed primary antibody deficiency. About half of CVID patients develop chronic non-infectious complications thought to be due to intrinsic immune dysregulation, including autoimmunity, gastrointestinal disease, and interstitial lung disease (ILD). Multiple studies have found ILD to be a significant cause of morbidity and mortality in CVID. Yet, the precise mechanisms underlying this complication in CVID are poorly understood. CVID ILD is marked by profound pulmonary infiltration of both T and B cells as well as granulomatous inflammation in many cases. B cell depletive therapy, whether done as a monotherapy or in combination with another immunosuppressive agent, has become a standard of therapy for CVID ILD. However, CVID is a heterogeneous disorder, as is its lung pathology, and the precise patients that would benefit from B cell depletive therapy, when it should administered, and how long it should be repeated all remain gaps in our knowledge. Moreover, some have ILD recurrence after B cell depletive therapy and the relative importance of B cell biology remains incompletely defined. Developmental and functional abnormalities of B cell compartments observed in CVID ILD and related conditions suggest that imbalance of B cell signaling networks may promote lung disease. Included within these potential mechanisms of disease is B cell activating factor (BAFF), a cytokine that is upregulated by the interferon gamma (IFN-γ):STAT1 signaling axis to potently influence B cell activation and survival. B cell responses to BAFF are shaped by the divergent effects and expression patterns of its three receptors: BAFF receptor (BAFF-R), transmembrane activator and CAML interactor (TACI), and B cell maturation antigen (BCMA). Moreover, soluble forms of BAFF-R, TACI, and BCMA exist and may further influence the pathogenesis of ILD. Continued efforts to understand how dysregulated B cell biology promotes ILD development and progression will help close the gap in our understanding of how to best diagnose, define, and manage ILD in CVID.